2009
DOI: 10.1007/s00127-009-0499-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of illicit and non-medical use of psychotropic drugs in Japan

Abstract: The present study confirmed lower prevalence of drug use in Japan than in other countries, such as the United States. However, the non-medical use of psychotropic drugs seems more common in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 12 publications
4
24
2
Order By: Relevance
“…[8][9][10][11][12][13][14] In Japan, because of the low prevalence of injection drug use in the general population (lifetime prevalence of illicit drug use as a whole in 2009 was only 2.9%), coinfection with HCV in patients with HIV-1 infection is rare. [15][16][17][18] Recently, however, at our clinic, the AIDS Clinical Center, Tokyo, there has been a surge in the rate of acute HCV infection among men who have sex with men (MSM) with HIV-1 infection who deny using injection drugs. The AIDS Clinical Center is one of the largest referral centers for HIV care in Japan with patients mostly comprising MSM.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14] In Japan, because of the low prevalence of injection drug use in the general population (lifetime prevalence of illicit drug use as a whole in 2009 was only 2.9%), coinfection with HCV in patients with HIV-1 infection is rare. [15][16][17][18] Recently, however, at our clinic, the AIDS Clinical Center, Tokyo, there has been a surge in the rate of acute HCV infection among men who have sex with men (MSM) with HIV-1 infection who deny using injection drugs. The AIDS Clinical Center is one of the largest referral centers for HIV care in Japan with patients mostly comprising MSM.…”
Section: Introductionmentioning
confidence: 99%
“…However, illicit drug users are one of the “difficult to reach” populations and it is difficult to obtain accurate data on them [19]. It is especially difficult in Japan to collect data on illicit drug users, because of a strong government policy against illicit drug use and extremely low lifetime prevalence of illicit drug use in the general population (2.9% in 2009 according to the Nationwide General Population Survey on Drug Use and Abuse) [20,21] ( http://www.ncnp.go.jp/nimh/pdf/h21.pdf . in Japanese) ( http://www.mhlw.go.jp/bunya/iyakuhin/yakubuturanyou/torikumi/dl/index-04.pdf .…”
Section: Introductionmentioning
confidence: 99%
“…Families may play a restrictive role by preventing patients from using substances; as the disability pension from the governments is generally meagre, the patients may not be able to afford the substances [35,44]. Further, in some countries, the laws governing the use of illicit substances are quite strict [9]; patients with severe mental disorders may find it hard to obtain substances in this background. Further, adverse attitudes of the society towards the use of both licit and illicit substances may act as deterrents by adding to the stigma of having a mental disorder, particularly in women, in these countries.…”
Section: Smoking Among Patients With Schizophreniamentioning
confidence: 97%
“…Tominaga et al [9] reported the prevalence of illicit substance use and nonmedical use of prescription drugs as part of the Japanese part of the World Mental Health Survey (WMHSJ). The rates of lifetime use of illicit drugs including cannabis and cocaine were not more in those with psychiatric comorbidity than those without.…”
Section: Studies Of Substance Use Disorders Among Individuals With Psmentioning
confidence: 99%